The life Batangas celebrates - Medina, Susan Calo.; Quintos, Floy.; GMA 7 (Television station : Quezon City).; Philippines. Department of Tourism; Travel Time (Television program). (Manila Travel Time, 1996)
Features the Batanguenos in the celebration of their life that are their own through festivals and songs. Discover the architectural buildings and houses in Batangas.
Documentary.
VHS.
Keywords: Batanguenos; Architecture, Domestic -- Philippines -- Batangas; Batanguenos -- Social life and customs; Batangas (Philippines) -- Description and travel